2002
DOI: 10.1046/j.1365-2958.2002.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of F‐pilin reveals domains for pilus assembly, phage infection and DNA transfer

Abstract: Summary The F‐pilus has been implicated in recipient cell recognition during the establishment of a stable mating pair before conjugation as well as forming part of the conjugative pore for DNA transfer. The F‐pilus is the site of attachment of the filamentous phages (M13, f1 and fd), which attach to the F‐pilus tip, and the RNA phages, R17 and Qβ, which attach to different sites exposed on the sides of the pilus. R17 has been shown to undergo eclipse, or capsid release, outside the cell on pili attached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…This can be misleading. As we have shown here for the G69C F-pilin mutant, and as Grossman & Silverman (1989) and Manchak et al (2002) have also shown, altered F-pilins can be incorporated into filaments that fail to bind RNA bacteriophage. Such ambiguities might be minimized by using cysteine-reactive fluorescent dyes, rather than fluorescent bacteriophage, in conjunction with cysteine-containing F-pili.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…This can be misleading. As we have shown here for the G69C F-pilin mutant, and as Grossman & Silverman (1989) and Manchak et al (2002) have also shown, altered F-pilins can be incorporated into filaments that fail to bind RNA bacteriophage. Such ambiguities might be minimized by using cysteine-reactive fluorescent dyes, rather than fluorescent bacteriophage, in conjunction with cysteine-containing F-pili.…”
Section: Discussionsupporting
confidence: 73%
“…The effects of the G69C mutation can not be attributed to the presence of cysteine at this locus since the G69D mutation had much the same effects . Interestingly, neither we nor Manchak et al (2002), nor the more limited study by , identified F-pilin missense mutants that significantly reduced Ff bacteriophage sensitivity and DNA donor activity without also reducing or abolishing RNA bacteriophage sensitivity. One explanation for these data is that donor activity and DNA bacteriophage sensitivity are relatively robust functions with respect to modest alterations to F-pilin structure, whereas RNA bacteriophage infection is more sensitive.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations